115 Impact of early education in children commencing ALL treatment on physiotherapy referrals. (23rd February 2023) - Hughes, Kelly; Waller, Lucy; Bell, Daniel
Abstract : Background: An increase in the number of outpatient physiotherapy referrals for patients with Acute Lymphoblastic Leukaemia (ALL) was noticed between 2019 and 2021. This increase in referrals to Physiotherapy prompted our team to review the service to ensure we were providing optimal patient care, whilst evaluating staffing resource capacity and efficiency. Problem statement: The intention was to meet every parent/carer who had a child or young person (CYP) with a new diagnosis of ALL. We planned to introduce the role of Physiotherapy, provide information/advice regarding treatment side effects and to promote early activity and exercise. The aim to see whether this might reduce the impact of some of the side effects during initial ALL Chemotherapy treatment blocks, and/or increase understanding for parents of expected side effects of treatment, thereby reducing the number of physiotherapy referrals and improving staffing resources. Method: Our patient group were CYP with newly diagnosed ALL, between initial chemotherapy treatment blocks of Induction to the end of Consolidation. We audited the number of outpatient referrals to Physiotherapy from January 2021 to September 2021; this group did not receive any proactive early intervention or advice from Physiotherapy following their diagnosis which was standard care. Referrals were re-audited from September 2021 to April 2022; during this time we met all parents/carers of CYP with a new ALL diagnosis and provided early intervention. Conclusion: There was minimal impact on the number of outpatient referrals following early intervention, despite positive feedback from physiotherapists and families involved. On reflection we considered whether we provided the intervention at an optimal time and if the intervention was delivered in the most appropriate format. We are currently auditing whether providing information on Day 15 of treatment, as opposed to immediately following diagnosis, may have more impact on the number of outpatient physiotherapy referrals.